Efficacy, safety, and drug survival of patients with psoriasis treated with IL-17 inhibitors - brodalumab, ixekizumab, and secukinumab: real-world data from the Czech Republic BIOREP registry - Kojanova, Martina; Hugo, Jan; Velackova, Barbora; Cetkovska, Petra; Fialova, Jorga; Dolezal, Tomas; Tichy, Martin; Gkalpakiotis, Spyridon (Journal of dermatological treatment, 2022)
BACKGROUND: Real-world data on the use of interleukin-17 (IL-17) inhibitors for the treatment of psoriasis are limited. OBJECTIVE: To evaluate and compare the efficacy, safety, and drug survival of IL-17 inhibitors. METHODS: This retrospective study analyzed the BIOREP registry data of patients treated with at least one IL-17 inhibitor (secukinumab, ixekizumab, and brodalumab). RESULTS: In total, 949 patients were included. The improvement in PASI score was significant for all drugs, and the proportion of patients achieving PASI 75, 90, and 100 after both 3 and 24 months of therapy was highest for brodalumab, followed by ixekizumab and secukinumab. The Dermatology Life Quality Index score decreased to ˂3 after 3 months and to ˂2 after 24 months of therapy for all inhibitors. Loss of effectiveness was the major reason for discontinuation in 17.2% of patients, followed by adverse events in 3.2% of patients. The drug survival probability was the highest for brodalumab, followed by ixekizumab and secukinumab. Negative predictors for treatment discontinuation were obesity and the number of treatment lines, whereas a positive predictor was the presence of concomitant psoriatic arthritis; sex had no influence. CONCLUSION: This real-life study demonstrated the effectiveness and good safety profile of all currently available IL-17 inhibitors.
Keywords: stupeň závažnosti nemoci; interleukin-17; Registries; Česká republika; Antibodies, Monoclonal; monoklonální protilátky; registrace; retrospektivní studie; lidé; Severity of Illness Index; psoriáza; Psoriasis; Interleukin-17; Retrospective Studies; Czech Republic; Treatment Outcome; výsledek terapie; Humans